TANGGUNG JAWAB AKUNTAN PUBLIK DALAM PEMBUATAN PROSPEKTUS PADA KEGIATAN DI PASAR MODAL - Arya Wahyudi Karditha, Inocencio; Westra, I Ketut; Purwanti, Ni Putu (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 11, November 2013, 2013)
The capital market is a monetary institution that connecting the owner of the funds and those in need of the funds. The owner of the funds is the investor and those in need of the funds is the public company. The principle of transparency (disclosure) is known in capital market activities. To ensure the principle of transparency in the capital market, public companies supported by professionals who assisted the prospectus, written information which about public offering. Capital market particular professions as public accountants who have to examine and give an opinion on the financial statements is expected to deliver their opinion according to the material facts of a company. Therefore, this paper will explain the position and the responsibilities of public accountants in disclosure constructing the prospectus on the capital markets activities.
Keywords: Disclosure Principle, Prospectus, Public Offering, Public Accountant